Comparative analysis of RAPD, RFLP and PFGE for the Characterization of Pathogenic Vibrio parahaemolyticus Isolated from Seafood and Coastal Environment - Ayyappan, Minimol V.; Kishore, Pankaj; Nadella, Ranjith K.; Panda, Satyen K.; Nayak, B. B.; Prasad, M, Mukteswar; Kumar, H. Sanath (Fishery Technology, 2019)
Vibrio parahaemolyticus is ubiquitous in coastal marine environment. Certain strains of V. parahaemolyticus are pathogenic to humans and harbors either or both thermostable direct hemolysin (tdh) gene and tdh related hemolysin (trh) gene. Pathogenic V. parahaemolyticus isolates from the aquatic environment from Mumbai, India were characterized with respect to their virulence genotypes by employing random amplified polymorphic DNA (RAPD), restriction fragment length polymorphism (RFLP) and pulsed field gel electrophoresis (PFGE). Out of 140 samples, twenty five samples harboured virulent V. parahaemolyticus. Pandemic group specific PCR assays viz., GSVP, GSOLD, GSOK, ORF8 and PGS PCR showed differential performances which revealed difficulties in the confirmation of pandemic clone from environmental samples. Results from the molecular characterization employing RAPD and RFLP indicated that the PGS PCR positive isolates (2) showed identical banding pattern in RFLP analysis, whereas GS:OK positive isolates (4) showed similar RAPD banding pattern with 80% similarity among 11 pathogenic strains studied. However, in whole genome comparison by PFGE using notI restriction enzyme, these isolates were scattered in different groups at 40% similarity level. This study suggests that the genetically diverse pathogenic strains of V. parahaemolyticus with characteristic of pandemic clones are present in the coastal environment.